New Record of an Arboreal Snail Rhachistia bengalensis from Sankarpur Reserved Forest, West Bengal and Its Implication in small Protected Areas Management - Debnath, Partha; Datta, Rana; Sen Sarkar, Neera (Indian Forester, 2025)
This study documents the first recorded presence of an arboreal snail Rhachistia bengalensis in the Sankarpur Reserved Forest, expanding its known geographical distribution. Additionally, it highlights the ecological correlates of this record and discusses its implications in the management of small reserved forests. Most arguments favour the superiority of large Protected Areas (PA) over small reserves. These arguments are justified primarily on the basis of island biogeography theory, focusing on importance of sustaining viable populations of top predators but many times overlook the evidence in favour of the importance of strategically placed smaller species in small reserved areas which are anthropogenically altered or disturbed. In fact, small reserved forests though with common features of large geographical expanses, are seldom evaluated for their synergistic contribution to biodiversity conservation. This study shows that small reserved areas are prevalent features of landscapes, and suggests how they should be studied and managed at multiple scales, applying systematic conservation planning in a spatially hierarchical manner. This approach can help ensure that small, local projects contribute to global goals. With the above consideration, the present study focusses on the sudden appearance of a new arboreal snail in a small reserved forest under the Nadia- Murshidabad Division in West Bengal.